(untitled) (Web of Teachers: Inderscience Research, 2025)
The article demonstrates the significant role of differential equations in teaching physics, electrical engineering, and electronics, while also providing scientific insights into the laws of switching when connecting and disconnecting an electrical circuit from a source. According to the authors, interdisciplinary connections play an important role in solving problems in the teaching of physics and technical sciences.